The elements of hydrostatics - Loney, S. L. ([S.l.] : Cambridge University Press, 1951)
Shipped from UK, please allow 10 to 21 business days for arrival. 253pp. plus 12pp. of answers at rear. Pitt Press Mathematical Series. Good clean copy.